2020
DOI: 10.1177/1049909119901133
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Near the End of Life in Onco–Hematological Adult Patients

Abstract: Objective: The use of chemotherapy near the end of life is not advisable. There are scarce data in Europe but shows signs of aggressiveness. We designed this study to analyze the proportion of onco–hematological patients receiving chemotherapy within their last 2 weeks of life as well as starting a new chemotherapy regimen in the 30 days prior to death. Methods: A retrospective observational study was conducted in a tertiary hospital. Adults who died of an onco-hematological neoplasia while hospitalized betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…PC integration may also result in cost savings, considering that a substantial proportion of patients with HM have been shown to receive chemotherapy in their last 2-4 weeks of life. 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC integration may also result in cost savings, considering that a substantial proportion of patients with HM have been shown to receive chemotherapy in their last 2-4 weeks of life. 38…”
Section: Discussionmentioning
confidence: 99%
“…PC integration may also result in cost savings, considering that a substantial proportion of patients with HM have been shown to receive chemotherapy in their last 2-4 weeks of life. 38 Various models have been proposed to facilitate PC integration in the care of patients with HM. 39,40 In this study, the primary team (ie, either oncology or intensive care) requested consults, and thus, bias was likely introduced because of the assessment by the primary team in determining which patients were most in need of PC consultation.…”
Section: Jco Oncology Practice E691mentioning
confidence: 99%
“…Some authors believe that chemotherapy in the last weeks of life is a lowquality factor in the assessment of patient care [12]. Nevertheless, urgent palliative chemotherapy is a treatment option for advanced disease in hospitalized patients of cancer, provided that there is some expectation of a positive response with an increase in survival or improvement of symptoms [3][4][5]13].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the natural history of cancer and the healthcare system's access inequalities, we often encounter patients with advanced disease or poor clinical performance. Hence, we may nd patients with end-stage cancer who have undergone several lines of treatment, with years of disease evolution; we may also come across patients with low performance status but with a recent diagnosis and no opportunity yet to be evaluated by a specialist and receive adequate cancer treatment [2][3][4][5]. It is known that patients with cancer who are hospitalized tend to be more symptomatic and in a more advanced stage of the disease than patients undergoing outpatient treatment and follow-up [6].…”
mentioning
confidence: 99%
“…Previous research found reduced odds of aggressive care at EOL in older age cohorts regardless of sex [ 11 , 14 , 15 , 35 ]. One study of patients with hematologic and solid tumour malignancies found that female sex and age ≤45 years were associated with receipt of chemotherapy in the last 14 days of life, another indicator of aggressive EOL care [ 36 ]. Similarly, a study of lung cancer decedents found a stronger association between aggressive care at EOL and females under age 50, as compared to males [ 37 ].…”
Section: Discussionmentioning
confidence: 99%